Evaluation of calcium carbonate precipitation by Bacillus spp. isolated from Stingless bees products - Addenan, Nurul Asyiqin; Ngalimat, Mohamad Syazwan; Raja Abd Rahman, Raja Noor Zaliha; Donepudi,, Rakesh; Mohd Nasir, Noor Azline; Jaafar, Mohd Saleh; Sabri, Suriana (Universiti Kebangsaan Malaysia, 2023)
Microbiologically Induced Calcium Carbonate Precipitation (MICCP) through urea hydrolysis is the most effective way to precipitate a high concentration of calcium carbonate (CaCO3) within a short time. The MICCP process is used to remediate the micro-crack in the concrete. However, limited research has been conducted to determine CaCO3 precipitation by bacteria, especially in Malaysia. Here, Bacillus spp. isolated from the Malaysian stingless bee products were evaluated for CaCO3 precipitation. Bacillus spp. were selected for further study according to their ability to produce urease enzymes. The urease-positive Bacillus spp. were screened for CaCO3 precipitation 2 by culturing on both CaCO3 precipitation agar and broth media. The survivability of the urease positive Bacillus spp. in various temperatures, pH values, and NaCl concentrations were tested. Seven out of 11 Bacillus spp. were found as ureolytic bacteria. Among the ureolytic bacteria, bacteria belonging to the Bacillus subtilis species complex group showed the highest number of bacteria (36.4) that are capable of precipitating CaCO3. Bacillus stratosphericus PD6 and B. aryabhattai BD8 exhibited the largest CaCO3 precipitation zones (15 mm). Bacillus stratosphericus PD6 also precipitated the highest amount of CaCO3 (65 mg) and urease activity (0.197 U/mL). All the urease-positive Bacillus spp. were able to grow at 45°C, pH (8 to 12), and 5 NaCl. Only B. subtilis BD3 can withstand high temperatures up to 55°C and 15 NaCl concentration. In conclusion, Bacillus spp. isolated from stingless bee products showed the ability as the CaCO3 precipitating bacteria; suggesting its potential application in self-healing concrete.